The Correlation Between the Household Food Security and the Incidence of Stunting in Toddlers 6-59 Months in Seberang Ulu I Palembang - Sari, Indah Purnama; Ningsih, Windi Indah Fajar; Sari, Desri Maulina (Jurnal Ilmu Kesehatan Masyarakat, 2023)
Toddlers are one of the vulnerable groups experiencing stunting nutritional problems. Households with good food security can prevent toddlers from nutritional problems such as stunting. The purpose of this study was to analyze the relationship between food security and the incidence of stunting in toddlers in Palembang City, especially in the Seberang Ulu 1 area. The cross-sectional study designs with a sample of 200 toddlers aged 6-59 months in Seberang Ulu I District who were taken by purposive sampling. Data were analyzed of bivariate used the Chi-Square Test (crude) and multiple logistic regression analysis was used as a multivariate analysis (adjusted). The incidence of stunting under five occurs more in households with food insecure conditions, high food expenditure, low income and low maternal education. There was a relationship between household food security and the incidence of stunting (p<0.05) and there was no relationship between food expenditure, family income and mother's education with the incidence of stunting in toddlers in Seberang Ulu I District (p>0.05). Multivariate analysis showed that toddlers in households in food insecure conditions had a 1.7 times higher risk of experiencing stunting than toddlers in households in food secure conditions after controlling for family income. Food insecurity is a risk factor for stunting in toddlers. Based on the results of this study, it is suggested that the government provide guidance to increase family income through improving entrepreneurship skills for families in Seberang Ulu 1 to prevent stunting.